Análise da influência de superfícies protetoras na durabilidade do concreto para uso em meio agressivo: uma abordagem topográfica e da estrutura do material - Joana Darc da Silva Pinto (2006)
The concrete is one of the most used materials in the world and it has been object of many works, which have been providing a large development of its use. The deterioration of concrete has been responsible for many damages on structural elements in civilconstruction, owned to durability problems, pointing out the urgency of developing new researches about the effects of superficial corrosion of concrete. This work studies the influence of surface coating in the durability of concrete under aggressive environment, through 3D topographic approach, proposing a new methodology to evaluate the performance of different kinds of protections in concrete durability.Concrete mix designs were produced, in order to select a concrete with a low water/cement ratio, high resistance and high impermeability, which are requests for durability. The concrete selected was then protected with surface coating (acrylic, sealer/acrylic and chlorinated rubber) and exposed to an acid aggressive environment (H2SO4 a 2.5%) by immersion. The concrete was evaluated through compressive strength,impermeability test, MEV/EDS and profilemetry technique. The performance of the protections was evaluated through surface profilemetry, which produced topographic images and statistical data (surface parameters). This technique supplies 3D topographical images, allowing the comparison of the superficial textures of the concrete, with and without protection, before and after chemical attack. Through this procedure it was possible to evaluate the effectiveness of surface coatings applied to concrete submitted to chemical attack and, also, to determinate which of the analyzed surface coatings offers more protection. This research demonstrates that profilemetry is anaccurate and efficient technique in the studies of concrete surface and can be very useful in researches on concrete durability, still enlarging the interchange between Materials Engineering and Civil Engineering.